2012
DOI: 10.1175/jhm-d-10-05027.1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Spatial Distribution of Snow Cover in the Dudhkoshi Region of the Nepal Himalayas

Abstract: In this study, a distributed biosphere hydrological model with three-layer energy-balance snow physics [an improved version of the Water and Energy Budget-based Distributed Hydrological Model (WEB-DHM-S)] is applied to the Dudhkoshi region of the eastern Nepal Himalayas to estimate the spatial distribution of snow cover. Simulations are performed at hourly time steps and 1-km spatial resolution for the 2002/03 snow season during the Coordinated Enhanced Observing Period (CEOP) third Enhanced Observing Period (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 63 publications
2
69
0
Order By: Relevance
“…These mapping exercises indicated that remote-sensing (RS) data and geographic information system (GIS) tools are more reliable for snow cover mapping. Further snow cover and glacier change research has been carried out using various methods, datasets and techniques in Nepal in a major part of the Himalayan regions (Armstrong 2010;Bolch et al 2012), as well as at the national level (Shrestha and Joshi 2009;Bajracharya et al 2014) or at a smaller scale (Maskey et al 2011;Shrestha et al 2012;Kuhle 2014;Shea et al 2014). The overall small-scale mapping of various classes of LULC in Nepal is summarized in the Table 2, with LULC categories, spatial and temporal coverage, sources of data and references.…”
Section: Study Area Sources Of Data and Methodsmentioning
confidence: 99%
“…These mapping exercises indicated that remote-sensing (RS) data and geographic information system (GIS) tools are more reliable for snow cover mapping. Further snow cover and glacier change research has been carried out using various methods, datasets and techniques in Nepal in a major part of the Himalayan regions (Armstrong 2010;Bolch et al 2012), as well as at the national level (Shrestha and Joshi 2009;Bajracharya et al 2014) or at a smaller scale (Maskey et al 2011;Shrestha et al 2012;Kuhle 2014;Shea et al 2014). The overall small-scale mapping of various classes of LULC in Nepal is summarized in the Table 2, with LULC categories, spatial and temporal coverage, sources of data and references.…”
Section: Study Area Sources Of Data and Methodsmentioning
confidence: 99%
“…The snowmelt model applied in this study is the WEB-DHM-S (Water and Energy Budget -based Distributed Hydrological Model with improved snow physics) 11,12) . WEB-DHM-S is the improved version of WEB-DHM 13) in its snow physics in the distributed biosphere hydrological modeling framework.…”
Section: Methods (1) Distributed Snow Model (Web-dhm-s)mentioning
confidence: 99%
“…The bulk density of ice for new snowfall is calculated following the formulation used in the CROCUS snow model 15) . The detailed description of the model equations and snow physics is comprehensively described by Shrestha et al 9,10) . A hillslope-driven runoff scheme employing a kinematic wave flow routing method is adopted in calculating runoff.…”
Section: Modelmentioning
confidence: 99%
“…Model output is taken as the maximum snow extent over 8-day, corresponding to the dates of the MODIS dataset. A model-output pixel was determined snow covered when the snow depth is greater or equal to 4cm 10) . As evident from the Fig.…”
Section: Model Performance Evaluationmentioning
confidence: 99%
See 1 more Smart Citation